การเยียวยาเหยื่ออาชญากรรมข้ามชาติที่ได้รับผลกระทบตามอนุสัญญาสหประชาชาติว่าด้วยการต่อต้านอาชญากรรมข้ามชาติที่จัดตั้งในลักษณะองค์กร ค.ศ.2000 : ศึกษากรณีการพัฒนากฎหมายและแนวปฏิบัติเกี่ยวกับการเยียวยาเหยื่ออาชญากรรมข้ามชาติของประเทศไทย - สุภัทรา สุขปาณี (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
For 13 years, After Thailand signed the United Nations Convention Against Transnational Organized Crime 2000 at Italy and following three Protocols as follows ; Protocol to Prevent, Suppress and Punish Trafficking in Person, Especially Women and Children, the Protocol Against the Smuggling of Migrants by Land, Sea and Air and the Protocol to combat the production and trafficking of illegal weapons. Thailand had amended the law to comply with this Convention and three Protocols. But the laws of Thailand which are enacted to help and remedy the victims from Transnational Organized Crimes are not governed issues of Convention and Protocols. Those caused suffering to the victims. And enforcement of Thailand are not cover and without the establishment the relevant government authorities directly to response the victims. With the mentions above the remedies of victim of Thailand from Transnational Organized Crimes are not yet comply with the United Nations Convention Against Transnational Organized Crime 2000 above. After studying and analyzing, it can be found the laws and the enforcement of the law mechanism only not sufficient to resolve the problems to remedy the victims. Therefore, other measures and mechanism of Thai Government and private organization can play the significant roles in order to increase efficiency in remedy the victims of this Convention.